Cover Picture: Highly Efficient Phase Boundary Biocatalysis with Enzymogel Nanoparticles (Angew. Chem. Int. Ed. 2/2014). Issue 2 (2nd December 2013) - Kudina, Olena; Zakharchenko, Andrey; Trotsenko, Oleksandr; Tokarev, Alexander; Ionov, Leonid; Stoychev, Georgi; Puretskiy, Nikolay; Pryor, Scott W.; Voronov, Andriy; Minko, Sergiy
<x xml:space="preserve">Abstract</x> An enzymogel that shows a novel type of phase‐boundary biocatalysis is described by S. Minko, A. Voronov, et al. in their Communication on page 483 ff. The enzymogel particles combine biocatalysis involving enzymes in the particle, stimuli‐triggered extracapsular biocatalysis, biocatalytic conversion of substrates contacting the enzymogel when the enzymes engulf the substrate, and stimuli‐triggered reattachment of the released enzymes for their reuse (cover image courtesy of Ella Marushchenko).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>